Singlet Oxygen Metabolism: From Genesis to Signaling - Dogra, Vivek (Front Plant Sci, 2020)
Singlet oxygen ((1)O(2)) is an excited state of molecular oxygen with an electron spin shift in the molecular orbitals, which is extremely unstable and highly reactive. In plants, (1)O(2) is primarily generated as a byproduct of photosynthesis in the photosystem II reaction center (PSII RC) and the light-harvesting antenna complex (LHC) in the grana core (GC). This occurs upon the absorption of light energy when the excited chlorophyll molecules in the PSII transfer the excess energy to molecular oxygen, thereby generating (1)O(2). As a potent oxidant, (1)O(2) promotes oxidative damage. However, at sub-lethal levels, it initiates chloroplast-to-nucleus retrograde signaling to contribute to plant stress responses, including acclimation and cell death. The thylakoid membranes comprise two spatially separated (1)O(2) sensors: β-carotene localized in the PSII RC in the GC and the nuclear-encoded chloroplast protein EXECUTER1 (EX1) residing in the non-appressed grana margin (GM). Finding EX1 in the GM suggests the existence of an additional source of (1)O(2) in the GM and the presence of two distinct (1)O(2)-signaling pathways. In this review, we mainly discuss the genesis and impact of (1)O(2) in plant physiology.